2017
DOI: 10.1186/s12887-016-0772-x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal screening for congenital adrenal hyperplasia in Southern Brazil: a population based study with 108,409 infants

Abstract: BackgroundCongenital adrenal hyperplasia (CAH) is an autosomal recessive disorder associated with inborn errors of steroid metabolism. 21-hydroxylase enzyme deficiency occurs in 90 to 95% of all cases of CAH, with accumulation of 17 hydroxyprogesterone (17-OHP). Early diagnosis of CAH based on newborn screening is possible before the development of symptoms and allows proper treatment, correct sex assignment, and reduced mortality rates. This study describes the results obtained in the first year of a public C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 31 publications
3
15
1
3
Order By: Relevance
“…There have been several strategies implemented by screening programs to improve the specificity of CAH screening. Improvement in the specificity was observed when the cut-off level of 17OHP was stratified based on either gestational age or birth weight and/or age of sampling [ 1 , 14 , 16 , 18 , 37 , 38 , 39 , 40 ]. Although gestational age stratification of 17OHP concentration was shown to give higher specificity, birth weight stratification has been more widely used [ 22 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several strategies implemented by screening programs to improve the specificity of CAH screening. Improvement in the specificity was observed when the cut-off level of 17OHP was stratified based on either gestational age or birth weight and/or age of sampling [ 1 , 14 , 16 , 18 , 37 , 38 , 39 , 40 ]. Although gestational age stratification of 17OHP concentration was shown to give higher specificity, birth weight stratification has been more widely used [ 22 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Newborn screening for CAH began with the development of a radioimmunoassay by Pang et al, 1977 [ 10 ] measuring 17 α-hydroxyprogesterone(17OHP) using blood on microfilter paper. Since then, worldwide CAH screening or pilot studies have ensued [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Newborn screening for CAH is aimed at identifying newborns with SWCAH promptly to prevent a life threatening adrenal crisis, thus reducing morbidity and mortality in affected individuals [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…An increase in early access to this test was found from 2016 to 2017, with associations between "child's age" and "place of collection" for both years, and "type of user" for 2016. Studies have highlighted the importance of early diagnosis of the diseases investigated in biological neonatal screenings, with the purpose of providing appropriate treatment in order to reduce negative repercussions on children's health (2)(3)(4)(5)(14)(15)(16) .…”
Section: Evaluations Of Coverage In Other Brazilian Regionsmentioning
confidence: 99%
“…However, the high frequency of falsepositive (FP) results remains a major issue, especially in preterm newborns. The positive predicted value (PPV) has been described to be ∼1.6-2.3% in screened Brazilian cohorts (8)(9)(10)(11). A recent pilot study conducted in Saõ Paulo found a PPV of 5.6 and 14.1% upon using the 99.8th percentile in samples collected until and after 72 h of life, respectively (3).…”
Section: Introductionmentioning
confidence: 99%